Perspektif Hukum Islam Terhadap Biaya Penalty Deposito Mudharabah - Heru Maruta; Imron Imron (JPS (Jurnal Perbankan Syariah), 2020)
This research aims to determine the practice of penalties for taking time Mudharabah deposits before maturity in the perspective of Islamic law at Bank Syariah Mandiri Bengkalis Sub-Branch Office. This research is based on primary and secondary data. Based on the results of the study note that there are customers of Bank Syariah Mandiri Bengkalis Sub-Branch Office who take deposits Mudharabah before maturity, then the customer will be subject to a penalty against funds deposited. By looking at the practice of penalties carried out by Bank Syariah Mandiri Bengkalis Sub-Branch Office is not appropriate and deviates from the theories that apply in Islamic economics. This is because the penalty agreement is not written clearly in the agreement document.